Thermodynamic reassessment of the La–Mn system - Wang, Yaru; Hu, Biao; Liu, Shuhong; Du, Yong (Journal of Mining and Metallurgy, Section B: Metallurgy, 2012)
The binary La–Mn system is investigated by CALPHAD approach. The experimental phase diagram and thermodynamic data available in the literature are critically reviewed and assessed using the thermodynamic models for the Gibbs energies of individual phases. A set of consistent thermodynamic data for the La–Mn system is obtained by optimization of the selected experimental data. The miscibility gap is no more existent in the optimized phase diagram. The calculated phase diagram agrees well with the experimental data.